UNVEILING THE ROLE IN SHAPING SUSTAINABILITY REPORTING IN THE MINING SECTOR - Ardhani, Chrystabelle Audrey; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2025)
The social and environmental responsibilities of companies have drawn public attention to their economic, social, and environmental performance. This has an impact on collective survival due to the effects caused by the company's operational activities. Therefore, companies are increasingly focusing on their surrounding environment by implementing CSR, which is reported through Sustainability Reporting Disclosure. This reporting is also influenced by corporate governance principles and the performance achieved. This research was conducted to provide empirical evidence on the influence of governance and corporate performance on sustainability reporting disclosure. The companies selected for the study are those in the mining industry that published sustainability reporting disclosures during the research period from 2019 to 2023. The research sample was chosen using purposive sampling, with a total of 19 companies out of 42 companies. The analysis that is used to test the research hypothesis is linear regression analysis. The results of the study show that the board of directors has a positive and significant influence on Sustainability Reporting Disclosure, while the audit committee, profitability, and leverage have no influence on Sustainability Reporting Disclosure. This research provides information to stakeholders regarding factors that can improve the information in corporate sustainability reports. From these findings, it can be seen that governance and corporate governance do not have a significant impact on sustainability reporting disclosure, suggesting that companies should focus not only on these factors but also consider other factors.